Slower progression of amyotrophic lateral sclerosis with external application of a Chinese herbal plaster–The randomized, placebo-controlled triple-blinded ALS-CHEPLA trial - Schröder, Sven; Wang, Mingzhe; Sima, Dandan; Schröder, Joana; Zhu, Xuying; Zheng, Xuanlu; Liu, Lin; Li, Tingying; Wang, Qiudong; Friedemann, Thomas; Liu, Te; Pan, Weidong (Frontiers in Neurology, 2022)
Background: Amyotrophic lateral sclerosis (ALS) is a chronic neurodegenerative disease characterized by gradually increasing damage to the upper and lower motor neurons. A definitive and efficacious treatment for ALS is not available, and oral intake in ALS patients with bulbar involvement is complicated due to swallowing difficulties. Hypothesis/Purpose: This study investigated whether the external plaster application of the herbal composition Ji-Wu-Li efficiently slows ALS progression because prior studies obtained promising evidence with oral herbal applications. Study Design: The randomised, triple-blinded study compared the efficacy, safety, and tolerability of applying Ji-Wu-Li plaster (JWLP) with placebo plaster (PLAP). Methods: In total, 120 patients with definite ALS, clinically probable ALS or clinically probable laboratory-supported ALS were randomised in a 1:1 ratio to receive JWLP or PLAP. Patients were treated and observed for 20 weeks. The primary outcome was the ALSFRS-R score, while the secondary outcomes were the ALS-SSIT score and weight loss. Results: The mean±SD decrease in the ALSFRS-R over 20 weeks differed by 0.84 points in a group comparison (JWLP, −4.44±1.15; PLAP, −5.28±1.98; p=0.005). The mean increase in the ALS-SSIT over 20 weeks differed by 2.7 points in a group comparison (JWLP, 5.361.15; PLAP, 8.06±1.72; p<0.001). The mean weight loss over 20 weeks differed by 1.65 kg in a group comparison (JWLP, −3.98±2.61; PLAP, −5.63±3.17; p=0.002). Local allergic dermatitis suspected as causal to the intervention occurred in 10 of 60 participants of the JWLP group and 9 of 60 participants in the PLAP group. Systemic adverse events were mild, temporary, and considered unrelated to the intervention. Conclusion: The JWLP showed clinical efficacy in the progression of ALS, as measured by the ALSFRS-R, ALS-SSIT and weight loss, in a randomised, placebo-controlled trial. Because skin reactions occurred in both groups, the covering material needs improvement. All of the Ji Wu Li herbal ingredients regulate multiple mechanisms of neurodegeneration in ALS. Hence, JWLP may offer a promising and safe add-on therapy for ALS, particularly in patients with bulbar involvement, but a confirmative long-term multicentre study is required.